2020
DOI: 10.3390/nu12123653
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Caffeine Ingestion on Cognitive Dual Task Performance during Assessment of Static and Dynamic Balance in Older Adults

Abstract: The present work aimed to evaluate the effect of 3 mg·kg−1 caffeine consumption on the standing and dynamic balance performance of older adults and sought to establish if caffeine ingestion can modulate the influence of a cognitive dual task on balance performance. Twelve apparently healthy participants (8 females) aged >65 years (72 ± 3.7 years) completed the study. Bipedal postural sway, four square step test, timed up and go, Y-balance (anterior reach only) and force-time characteristics of sit-to-stand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 97 publications
2
24
0
Order By: Relevance
“…Our findings correlate with some of the literature data, including a study done by Trunzo et al in 2014 [10], which found that energy drink consumption decreased academic performance in college students. Further, our results also aligned with those of Tallis J et al [22], where caffeine proved to be inefficient, enhancing balance and gait during cognitive dual tasks in an older group.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings correlate with some of the literature data, including a study done by Trunzo et al in 2014 [10], which found that energy drink consumption decreased academic performance in college students. Further, our results also aligned with those of Tallis J et al [22], where caffeine proved to be inefficient, enhancing balance and gait during cognitive dual tasks in an older group.…”
Section: Discussionsupporting
confidence: 91%
“…Following assessment of these eighteen full articles against the eligibility criteria, a further ten were excluded. Reference list screening resulted in one additional study, meaning a total of nine eligible studies were included in the systematic review [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the nine eligible studies, five investigated the effects of caffeine on human standing balance in a participant group aged less than 65 years (i.e., younger) [ 25 , 26 , 27 , 28 , 32 ]. Five studies included a participant group with an average age of 65 years or over (i.e., older) [ 27 , 29 , 30 , 31 , 33 ]. Swift and Tiplady (1988) was the only study to compare groups of younger and older participants [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations